Resistance to leaf rust in coffee cultivars - Sera, Gustavo Hiroshi; Sera, Tumoru; Fonseca, Inês Cristina de Batista; Ito, Dhalton Shiguer (Coffee Science - ISSN 1984-3909, 2010)
All the Coffea arabica L. cultivars developed by the IAPAR4 were resistant to rust (Hemileia vastatrix) when registered. However, with the appearance of new races these cultivars now present different resistance levels. The aim of this work was to assess the resistance to rust in coffee cultivars developed by the IAPAR. Resistance to the local leaf rust races was assessed in high disease intensity field conditions in August 2007. Twelve coffee cultivars, from IPR 97 to IPR 108, were evaluated. ‘IAPAR 59’ and ‘Catuaí Vermelho IAC 81’ were used as resistance and susceptibility standards, respectively. The experimental design was in randomized blocks with nine replications and plots with seven plants. A scale from 1 to 5, based on rust severity, was used to evaluate resistance. Yield evaluation was based on the harvest carried out in June 2007. The cultivars IAPAR 59, IPR 97, IPR 98, IPR 104 and IPR 105 were almost 100 % rust resistant, while IPR 99, IPR 101, IPR 102 and IPR 107 presented approximately 75% of plants with complete resistance. Thus, the resistance gene(s) is probably in heterozygous condition. The cultivars IPR 103 and IPR 108 may present incomplete resistance, while the IPR 100 presented similar susceptibility to ‘Catuaí Vermelho IAC 81’ and IPR 106 may also be susceptible.